2020
DOI: 10.1590/acb351202
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A acutely attenuates blood-brain barrier permeability, oxidative stress, inflammation and apoptosis in traumatic brain injury in rats1

Abstract: To investigate the therapeutic benefits of Hydroxysafflor yellow A (HSYA) on blood-brain barrier (BBB) vulnerability after traumatic brain injury (TBI) and identify its potential action of mechanisms on TBIinduced injuries. Methods: The rat TBI model was performed by using a controlled cortical impact device. The BBB permeability induced by TBI was measured through Evans Blue dye superflux and western blotting or polymerase chain reaction (PCR) for tight junctional proteins (TJPs). The post-TBI changes in oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For example, HSYA reduced oxidative stress and reversed the increase in Bax and caspase-3 from nephropathy in type 2 diabetic rats, and significantly increased the protein expression of Bcl-2 in renal tissue ( 15 ). In addition, in traumatic brain injury in rats, HSYA protected neural cells against oxidative stress and anti-apoptosis by inhibiting the protein expression level of Bax, caspase-3, and caspase-9, while increasing antioxidant enzyme concentrations ( 14 ). All of the aforementioned studies confirmed that HSYA has an essential role in anti-oxidative stress and anti-apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, HSYA reduced oxidative stress and reversed the increase in Bax and caspase-3 from nephropathy in type 2 diabetic rats, and significantly increased the protein expression of Bcl-2 in renal tissue ( 15 ). In addition, in traumatic brain injury in rats, HSYA protected neural cells against oxidative stress and anti-apoptosis by inhibiting the protein expression level of Bax, caspase-3, and caspase-9, while increasing antioxidant enzyme concentrations ( 14 ). All of the aforementioned studies confirmed that HSYA has an essential role in anti-oxidative stress and anti-apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is a type of traditional Chinese medicine that promotes blood circulation and provides pain relief. Hydroxysafflor yellow A (HSYA), a mono chalcone glycoside derived from safflower, is the main component of safflower yellow pigment ( 14 ). Lee et al ( 15 ) found that HSYA could protect the kidney by inhibiting oxidative stress injury and renal cell apoptosis induced by nephropathy in type 2 diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NF-κB signal in the antidiabetic activities of HSYA has not been previously reported. Figure 2 indicates that NF-κB signal plays an important role in the use of HSYA to treat other inflammatory diseases [29][30][31][32][33][34][35][36][37][38]. This might provide some research points to explore antiinflammatory mechanisms of HSYA in the treatment of diabetes and diabetes complications.…”
Section: Anti-inflammatory Signals In Antidiabeticmentioning
confidence: 99%
“…Possible Anti-Inflammatory Mechanisms in Antidiabetic Research of HSYA. In Figure2, organ damages treated by HSYA via the NF-κB pathway include brain damages such as ischemia reperfusion-injury, traumatic brain injury, ischemic stroke, and Alzheimer's disease (AD)[29][30][31][32]; lung injury such as fetal lung fibroblasts, chronic obstructive pulmonary disease, and acute respiratory distress syndrome…”
mentioning
confidence: 99%